SOCIO-EMOTIONAL SKILLS IN RURAL EDUCATION TEACHERS - Johnny Arango Mejía (LÍNEA IMAGINARIA, 2025)
Rural teachers face various difficulties. Some are inherent to the Colombian education system, but others are due to the specific characteristics of a rural context that presents challenges characteristic of these territories, such as long commutes over rough roads, high expectations from parents, intermittent educational services due to geographic and climatic conditions that limit the impact of educational activities, parents who respond intermittently to requests, and work schedules that require them to spend most of their time away from home. These situations generate emotional and psychological pressure on rural teachers. Therefore, it is imperative to recognize the importance of socio-emotional skills (SESS) to maintain a balance between work, personal, and family life. To this end, a qualitative research study was conducted using an argumentative approach and documentary analysis to support a theoretical construct on the importance of strengthening skills that allow teachers to face the challenges common in rural settings.